1997
DOI: 10.1001/archinte.1997.00440270067006
|View full text |Cite
|
Sign up to set email alerts
|

Broadband Ultrasound Attenuation Predicts Fractures Strongly and Independently of Densitometry in Older Women

Abstract: Broadband ultrasound attenuation predicts the occurrence of fractures in older women and is a useful diagnostic test for osteoporosis. The strength of the association between BUA and fracture is similar to that observed with bone mineral density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
155
1
17

Year Published

1998
1998
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 627 publications
(186 citation statements)
references
References 27 publications
13
155
1
17
Order By: Relevance
“…In the follow up study blood sample was collected from study group after 3 months therapy. The bone mineral density was measured at the midshaft tibia by Quantitative Ultrasound method [6]. Estimation of intact osteocalcin by EASIA method [7].…”
Section: Methodsmentioning
confidence: 99%
“…In the follow up study blood sample was collected from study group after 3 months therapy. The bone mineral density was measured at the midshaft tibia by Quantitative Ultrasound method [6]. Estimation of intact osteocalcin by EASIA method [7].…”
Section: Methodsmentioning
confidence: 99%
“…Although it has been previously described that overweight children are skeletally advanced (37), recent studies have observed that a high proportion of children with distal forearm fractures are overweight and have lower bone mass and bone area density (38)(39)(40)(41)(42)(43)(44)(45)(46). Since physical activity is strongly osteogenic during growth, diminished participation in weight-bearing exercise by overweight children could have an adverse effect on bone development.…”
Section: Discussionmentioning
confidence: 99%
“…The predictive power of ultrasound measurements by means of broadband ultrasound attenuation with regard to femoral and spinal fracture risk has been demonstrated several times in osteoporotic women (22,(39)(40)(41). However, most of the studies performed to predict fractures using QUS have been done using ultrasound in the calcaneus (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…In all these studies, QUS is a good predictor or discriminator of hip or non-spine fractures. 9,45,[47][48][49][50][51][52][53] In a meta-analysis of QUS and fractures, Marín et al reported the strength of association between QUS with non-spinal fractures to be similar to axial or peripheral BMD measurements. However, QUS was shown to be inferior to the association between BMD measured at the hip and hip fracture.…”
Section: Fracture Discriminationmentioning
confidence: 99%